Seduction without cause: uncovering explanatory neurophilia - Trout, J.D. (Trends in Cognitive Sciences, 2008)
Credibility is a cherished currency in science, but its cues can be counterfeit. A novel series of experiments by Weisberg and her colleagues show that non-expert consumers of behavioral explanations assign greater standing to explanations that contain neuroscientific details, even if these details provide no additional explanatory value. Here, we discuss the part that this ‘placebic’ information might play in producing a potentially misleading sense of intellectual fluency and, consequently, an unreliable sense of understanding.